2020
DOI: 10.1177/2042018820923474
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: PFKFB3, a key glucose metabolic enzyme regulated by pathogen recognition receptor TLR4 in liver cells

Abstract: Aims: Toll-like receptor 4 (TLR4) and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB3) are involved in the progress of inflammation and glucose metabolism. Here, we aimed to assess the relationship between TLR4 and PFKFB3 in liver cells. Methods: We detected the expression of TLR4 and PFKFB3 in both normal liver cell lines and liver cancer cell lines. Then, a small interfering RNA (siRNA) was used to knock down the expression of TLR4 and analyze the expression of PFKFB3 in the HL-7702 cell line. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…DNA topoisomerase 2-α (TOP2A) expression was restricted to the GCL. 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (F263) – an enzyme involved in the control of glycolytic flux [ 29 ] appeared to be present in the OPL, likely in horizontal cells, as well as in the GCL. Finally, staining with the antibody directed against glutamate ionotropic receptor kainate 2 (GRIK2) confirmed its presence in the INL and GCL, in line with previous findings [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA topoisomerase 2-α (TOP2A) expression was restricted to the GCL. 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (F263) – an enzyme involved in the control of glycolytic flux [ 29 ] appeared to be present in the OPL, likely in horizontal cells, as well as in the GCL. Finally, staining with the antibody directed against glutamate ionotropic receptor kainate 2 (GRIK2) confirmed its presence in the INL and GCL, in line with previous findings [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gene array data showed upregulation of PFKFB1-3 in transgenic liver, a key enzyme regulating glucose metabolism and promoting aerobic glycolysis. Hence, previous publications have shown that inhibitors targeting PFKFB3 have been found to suppress aerobic glycolysis, decrease glucose uptake, and induce cancer cell autophagy [ 31 ]. Moreover, consistently with previous publications transgenic expression of c-MYC also enhances the expression of mitochondrial GL and GLS for canonical glutaminolysis.…”
Section: Discussionmentioning
confidence: 99%
“…DNA topoisomerase 2-α (TOP2A) expression was restricted to the GCL. 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (F263) – an enzyme involved in the control of glycolytic flux (39) appeared to be present in the OPL, likely in horizontal cells, as well as in the GCL. Finally, staining with the antibody directed against glutamate ionotropic receptor kainate 2 (GRIK2) confirmed its presence in the INL and GCL, in line with previous findings (31).…”
Section: Resultsmentioning
confidence: 99%
“…DNA topoisomerase 2-α (TOP2A) expression was restricted to the GCL. 6phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (F263) -an enzyme involved in the control of glycolytic flux (39) appeared to be present in the OPL, likely in horizontal cells, as well as in the GCL.…”
Section: Pkg Target Validation For Retinal Localizationmentioning
confidence: 99%